Pharmacists' knowledge and attitudes toward medication therapy management service and the associated challenges and barriers for its implementation - Anan S. Jarab; Walid Al-Qerem; Tareq L. Mukattash; Shorouq R. Abuhishmah; Sojoud Alkhdour (Elsevier, 2022)
Background: The literature demonstrated a positive impact of medication therapy management (MTM) services provided by the pharmacists to improve the overall health outcomes. Nevertheless, limited data is available with regard to MTM service implementation by community pharmacists and its associated factors in Jordan. Objective: To evaluate community pharmacists' knowledge, attitude and practice of MTM service and to explore the challenges and barriers for its implementation. Methods: The present cross-sectional study utilized a validated online survey which was filled by community pharmacists in different areas across Jordan. In addition to the socio-demographic variables, the study questionnaire evaluated pharmacists' knowledge and attitudes towards MTM service, extent of MTM implementation and its associated challenges and barriers. Results: A total of 250 pharmacists completed the survey. The study pharmacists showed moderate knowledge level (median of the total knowledge score = 6 (4-7) out of 10) and positive attitude (median of the attitude score was 23 (19-26) out of 30) towards MTM services. The participating pharmacists recognized performing or obtaining necessary assessments of patient's health status as the most frequently provided MTM service (84.8%), while the least one was documenting the care delivered and communicating essential information to other healthcare providers (62%). Furthermore, collecting patient-related information was the most commonly recognized challenge to MTM service provision (36.8%), followed by referring the patient to a physician or consultant (36%) and collaboration with them (35.6%). The most reported barrier was negative physician attitudes (40.4%), followed by the lack of training on MTM provision (38.4%), and lack of adequate support staff (37.2%). Conclusion: Efforts are needed to enhance collaboration between pharmacists and other health care professional, to develop documentation systems that would preserve and facilitate access to patient information, and to implement appropriate training programs which aim to overcome the challenges and barriers for MTM implementation.